1996
DOI: 10.1016/s0014-5793(96)01344-0
|View full text |Cite
|
Sign up to set email alerts
|

Long‐chain fatty acids suppress the induction of urea cycle enzyme genes by glucocorticoid action

Abstract: In order to test the possibility that free fatty acids are the mediator of the abnormal expression of urea cycle enzyme genes in carnitine-deficient juvenile visceral steatosis (JVS) mice, the effects of fatty acids on urea cycle enzyme, carbamoylphosphate synthetase (CPS) and argininosuccinate synthetase (ASS), mRNA levels were examined in rat primary cultured hepatocytes. Addition of a synthetic glucocorticoid hormone, dexamethasone, caused increases in CPS and ASS mRNAs. Further addition of oleic acid suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 21 publications
1
25
0
2
Order By: Relevance
“…Other factors have been shown to positively or negatively regulate ASS1 expression. For example, cAMP increases ASS1 expression, while fatty acids cause suppression of this protein [41, 42], and factors such as hormones and pro-inflammatory stimuli are also known to regulate ASS1 expression [39, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…Other factors have been shown to positively or negatively regulate ASS1 expression. For example, cAMP increases ASS1 expression, while fatty acids cause suppression of this protein [41, 42], and factors such as hormones and pro-inflammatory stimuli are also known to regulate ASS1 expression [39, 43]. …”
Section: Discussionmentioning
confidence: 99%
“…Long-chain fatty acids have been reported to suppress the level of expression of genes encoding urea cycle enzymes. 16 This may contribute to the simultaneous reduction of urea synthesis and enhancement of lipid accumulation observed with the high insulin preconditioned cultures. On the other hand, downregulation of the FAS gene should reduce the level of fatty acid, which is a negative factor in the accumulation of intracellular TG.…”
Section: Relationship Between Lipid Accumulation and Urea Synthesis Imentioning
confidence: 99%
“…11 In addition, insulin downregulates long-chain acyl-CoA synthetase and its downregulation in turn negatively affects the gene expression level of urea cycle enzymes. 16 Amino acids may regulate gene expression of urea cycle enzymes via long-term control by modulating transcription factors (e.g., C/EBP family). 14 AARE, amino acid response element; UCE, upstream control element.…”
Section: Et Almentioning
confidence: 99%
“…Multiple factors have been shown to positively and negatively influence ASS gene and may be tissue specific. Several investigators have demonstrated that glucocorticoid, glucagon and cyclin AMP increase ASS expression whereas fatty acids repress ASS expression [58][59][60][61][62][63][64][65]. Insulin and growth hormone have negative influence on ASS in liver tissue but no effect in other tissue [66][67][68].…”
Section: Why Ass Is Not Expressed In Certain Tumor Types ?mentioning
confidence: 99%